Indirect effects of trading restrictions - Wang, Shujing; Yan, Hongjun; Zhong, Ninghua; Tang, Yizhou (Journal of Corporate Finance, 2024)
Stock market trading restrictions affect prices and liquidity directly through constraints on investors' transactions and indirectly by altering the information environment. We isolate this indirect effect by analyzing how stock market restrictions affect corporate bond yields. Exploiting the staggered reductions of trading restrictions in the Chinese stock market as a quasi-natural experiment, we document that the easing of trading restrictions on a firm's stock decreases its corporate bond spreads. This effect is stronger for firms with less transparency or lower credit ratings. Our evidence suggests that the effect is likely due to improved stock price informativeness.